PENDAMPINGAN BERBASIS MODAL SOSIAL UNTUK MENINGKATKAN KESEJAHTERAAN PEREMPUAN PADA ORGANISASI KPPI (KESATUAN PEREMPUAN PESISIR INDONESIA) DI BAGAN DELI KECAMATAN MEDAN BELAWAN - Bengkel Ginting; Muryanto Amin; Tonny Pangihutan Situmorang; Alwi Dahlan Ritonga (PT. Hasba Edukasi Mandiri, 2025)
Community service activities are one of the obligations that must be carried out by every lecturer in Higher Education. The proposed Community Service Activity is entitled: Social Capital-Based Mentoring to Improve Women's Welfare in the Kppi Organization (Indonesian Coastal Women's Union) in Bagan Deli, Medan Belawan District. Mentoring based on strengthening social capital for female fishers in the Indonesian Coastal Women's Union (KPPI) Medan organization is an empowerment strategy that aims to improve their welfare through the utilization of social networks, trust, and community norms. This program not only focuses on increasing individual capacity, but also strengthening social relationships that can open access to economic opportunities, resources, and social protection. By strengthening social capital, female fishers in the Indonesian Coastal Women's Union (KPPI) Medan organization can more easily share information, obtain support in facing challenges, and increase their competitiveness. In addition, this activity also encourages the active participation of female fishers in decision-making in the community, increases awareness of their rights, and strengthens solidarity and collaboration among group members. With the assistance provided, it is hoped that female fishermen will not only experience increased economic welfare, but also gain greater recognition in the fisheries sector and in their social life as a whole.